Comparing bi-national partnerships in Spain and Italy - Gaspar, S. (2018)
In recent decades, the number of bi-national partnerships has been rising in most EU countries, offering an opportunity to explore new family formations in greater depth. The aim of this paper is to provide a comparative overview of EU bi-national partnership profiles in Spain and Italy. An original survey of 766 intra-EU migrants (EIMSS, 2005) who moved to these Southern countries between 1974 and 2004 has been used to identify specific attributes of cross-national unions. A Multiple Correspondence Analysis (MCA) has been employed using several variables including migration motives, age, education, occupation and the presence of children within the household. The results allowed two dimensions to be constructed which were then used to perform a K-Means Cluster Analysis. A threefold typology emerged from the analysis: Love migrant bi-national partnerships (Type 1), Eurostars’ bi-national partnerships (Type 2), and Retired bi-national partnerships (Type 3). In light of these findings, the concluding discussion evaluates the role these profiles have in researching family and migration fields and the broader EU social integration process.